«Հայ գրականություն» (1911-1914 թթ.) - Խառատյան, Ա. Ա. (ՀՀ ԳԱԱ հրատ.)
Издававшийся в 1911-1914 гг. в Смирне журнал “Армянская литература“, редактором которого был З. Газазян, являлся одним из передовых периодических изданий в западноармянской действительности. Журнал свидетельствовал о высоком уровне развития армянской литературно-критической мысли Смирны. The magazine “Armenian literature” edited by Z.Gazazyan and published in the 1911-1914 in Smyrna was one of the leading periodical publications of the Western Armenian reality. The magazine published the works by Armenian and European writers, literary criticism, and papers on aesthetics. The magazine demonstrated a high level of the development of Armenian literary-critical thought in Smyrna.
Keywords: General Works; Պարբերական